2017
DOI: 10.12785/jifs/030101
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ZIS (Zakah, Infaq and Sadaqa) Distribution and Islamic Financial Institutions to MSMEs (Micro, Small, and Medium Enterprises) and Gross Regional Product Growth in East Java (2011-2014 Periods)

Abstract: Distribution and utilization are core activities of zakah management. It must be considered that Ameel zakah institutions' success is not merely founded on their capability to collect zakah fund, but also their ability to distribute and utilize it.This research is aimed at understanding impact of ZIS (zakah, infaq and sadaqa) distribution and Islamic Financial Institutions role on distributing their funds in East Java to Micro, Small and Medium Enterprises (MSMEs) and Gross Regional Product (GRP) of East Java.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…However, few studies that delve into this subject matter find several positive effects of Islamic microfinancing. For example, Hamidah et al (2017) found that access to Islamic microfinancing funds significantly affects the financial wellbeing of micro, small, and medium enterprises (MSME) in East Java, Indonesia. Besides, Hussaini (2017) reports that Islamic microfinance is an effective tool in reducing the extreme nature of poverty in northern Nigeria by providing interest-free credits to the disadvantaged but economically active population.…”
Section: Previous Studiesmentioning
confidence: 99%
“…However, few studies that delve into this subject matter find several positive effects of Islamic microfinancing. For example, Hamidah et al (2017) found that access to Islamic microfinancing funds significantly affects the financial wellbeing of micro, small, and medium enterprises (MSME) in East Java, Indonesia. Besides, Hussaini (2017) reports that Islamic microfinance is an effective tool in reducing the extreme nature of poverty in northern Nigeria by providing interest-free credits to the disadvantaged but economically active population.…”
Section: Previous Studiesmentioning
confidence: 99%
“…The distribution of IFI funds has a significant positive effect on MSME growth and GDRP growth in East Java. (Hamidah et al, 2017)…”
Section: Review Of Related Researchmentioning
confidence: 99%
“…This is what can affect economic growth. people (Hamidah et al, 2017). If the wealth is evenly distributed, it can reduce poverty and improve the economy (Fahmawati, 2019).…”
Section: Introductionmentioning
confidence: 99%